Personal earth station (PES) using VSAT technology / Adznan Shahidi Abd. Wahid and Barudin Sulaiman - Abd. Wahid, Adznan Shahidi; Sulaiman, Barudin (1992)
The potential of Satellite Communication is so great that it can change the entire fabric of society. In the 1990's decade the developement of Satellite Communication in Malaysia seems to be established to the up-to-date technology. Telekom Malaysia has taken this opportunity to enhance the utilisation of Satellite communication for local users. With the (introduction of VSAT) technology which uses small antennas to recieve mail, voice, data, television and computer communications via satellite, Malaysia will one of the advanced countries in providing telecommunication services. The scope of our project is to install, test, and commission a PES system for voice and data communication.